RELIGIOUS DISCOURSE IN THE ARAB MEDIA - KLAINA, MEKKI (Living Islam: Journal of Islamic Discourses, 2023)
The goal of oral and written Arab media is to send a message both inside and outside the country, to correct a misconception, or to spread a negative opinion about a particular aspect of politics, society, or the economy for a variety of reasons. Under the guise of modernizing the religious discourse, condemning its past, emancipating itself from religion, or restricting itself to international norms, this discourse had a presence in the Arab media. On the other hand, a different discourse seeks to portray Islam as a religion of peace, rights, and responsibilities as well as an embrace of others free from prejudice. The 2011 attack contributed to the growth of Islamophobia, which necessitates an inclusive conversation for understanding. This study will examine the consequences of this prevalent discourse on social cohesion in the Arab world. For this purpose, many institutions and scholars try to clarify the issue to improve social and religious life. Keyword: religious discourse; Islam; Arab media; Islamophobia